Modern Conservative Judaism : Evolving Thought and Practice - Dorff, Elliot N. (Book collections on Project MUSE., 2018)
"A Conservative Movement insider's guide to the evolution of Conservative Jewish thought and practice over the last half century, offering insight into the diverse (and occasionally contentious) thought processes behind the movement's most important laws, policies, and documents"--